Equilibrium, Thermoanalytical and Spectroscopic Studies to Characterize Phytic Acid Complexes with Mn(II) and Co(II) - De Carli, Ligia; Schnitzler, Egon; Ionashiro, Massao [UNESP]; Szpoganicz, Bruno; Rosso, Neiva Deliberali (Soc Brasileira Quimica, 2009)
Potentiometric studies were carried out to determine the binding degree of phytic acid with Co(II) and Mn(II) ions, in the absence of dioxygen. Equilibrium constants for all major complexes formed are reported, and the results are presented in the form of distribution diagrams showing the concentrations of individual complexes as a function of pH. The formation constants of the complexes show higher values for the species in which the ligand was more deprotonated. Potentiometric data indicates that the species [MH(4)L](6-), was totally formed at pH 7.0 and the complexes were synthesized from this data. A solid state complex of Mn(II) and Co(II) with phytic acid was synthesized. Thermogravimetry, differential scanning calorimetry, and infrared spectroscopy were used to investigate and characterize the thermal behavior of these compounds. The results led to information on the composition, dehydration, thermal stability and thermal decomposition of the isolated complexes.
Keywords: phytic acid; manganese (II) complexes; cobalt (II) complexes; equilibrium studies; thermal behavior